Adipose‐derived Mesenchymal Stem Cells Are Phenotypically Superior for Regeneration in the Setting of Osteonecrosis of the Femoral Head. Issue 10 (October 2015) - Wyles, Cody C.; Houdek, Matthew T.; Crespo‐Diaz, Ruben J.; Norambuena, German A.; Stalboerger, Paul G.; Terzic, Andre; Behfar, Atta; Sierra, Rafael J.
Abstract: Background: Bone marrow‐derived mesenchymal stem cells (bmMSCs) have been used as a cellular therapeutic option for treatment of osteonecrosis of the femoral head. However, use of bmMSCs as a treatment adjuvant for orthopaedic disorders in general has achieved limited success. Adipose‐derived MSCs (aMSCs) may be a more‐efficient regenerative cell source given their greater quantity and protection from physiologic stress. Questions / purposes: We asked the following questions in a paired analysis of MSCs from patients with osteonecrosis: (1) Is there a difference in proliferation potential between aMSCs and bmMSCs? (2) Is there a difference in osteogenic differentiation potential between aMSCs and bmMSCs? (3) Are genetic pathways differentially expressed between aMSCs and bmMSCs that may govern functional phenotypic discrepancies? Methods: Periarticular samples of adipose tissue and bone marrow from the femoral canal were obtained from 15 patients undergoing hip replacement for late‐stage (Steinberg Stages III‐VI) osteonecrosis. MSCs were isolated from both tissue sources and taken through a standardized 20‐day cell division protocol to establish cumulative cell count. They also were grown in osteogenic differentiation media for 14 days with subsequent measurement of alkaline phosphatase in units of optical density. RNA was isolated from aMSCs and bmMSCs in five patients to assess differentially expressed genetic pathways using the Affymetrix GeneChip ® Human Transcriptome Array 2.0 platform. Results: Proliferation capacity was increased by fourfold in aMSCs compared with bmMSCs after 20 days in culture. The mean difference in cumulative cell count was 3.99 × 10 8 cells (SD = 1.67 × 10 8 cells; 95% CI, 3.07 × 10 8 ‐4.92 × 10 8 cells; p < 0.001). Bone differentiation efficiency as measured by optical density was increased by 2.25‐fold in aMSCs compared with bmMSCs. The mean difference in optical density was 1.27 (SD = 0.34; 95% CI, 1.08‐1.46; p < 0.001). RNA transcriptome analysis showed 284 genes that met statistical (p < 0.05) and biological (fold change > 1.5) significance cutoffs for differential expression between cell populations. Subsequent network topology of differentially expressed genes showed alterations in pathways critical for musculoskeletal tissue development in addition to many nonspecific findings. Conclusions: aMSCs outperform bmMSCs in growth rate and bone differentiation potential in the setting of osteonecrosis, suggesting they may provide a more‐potent regenerative therapeutic strategy in this population. Differential expression of genes and cellular pathways highlighted in this study may provide therapeutic targets for cellular optimization or acellular treatment strategies. Clinical Relevance: aMSCs may provide a more robust cellular therapeutic than bmMSCs for treatment of osteonecrosis. Ideally, a well‐designed prospective study will be able to evaluate the efficacy of these cellular therapies side‐by‐side in patients with bilateral early stage disease.